Association of Uterine Leiomyoma with Type 2 Diabetes Mellitus in Young Women: A Population-Based Cohort Study - Ji-Hee Sung; Kyung-Soo Kim; Kyungdo Han; Cheol-Young Park (Diabetes & Metabolism Journal)
Background We investigated the association between uterine leiomyoma (UL) and incident type 2 diabetes mellitus (T2DM) in young women. Methods A nationwide population-based cohort study of 2,541,550 women aged between 20 and 40 years was performed using the National Health Information Database. Cox proportional hazards models were used to analyze the risk of incident T2DM according to the presence of UL and myomectomy. Results The mean age was 29.70 years, and mean body mass index was 21.31 kg/m2. Among 2,541,550 participants, 18,375 (0.72%) women had UL. During a median 7.45 years of follow-up, 23,829 women (0.94%) were diagnosed with T2DM. The incidence of T2DM in women with UL (1.805/1,000 person-years) was higher than in those without UL (1.289/1,000 person-years). Compared with women without UL, women with UL had a higher risk of incident T2DM (hazard ratio, 1.216; 95% confidence interval [CI], 1.071 to 1.382). Women with UL who did not undergo myomectomy had a 1.505 times (95% CI, 1.297 to 1.748) higher risk for incident T2DM than women without UL. However, women with UL who underwent myomectomy did not have increased risk for incident T2DM. Conclusion Young women with UL were associated with a high risk of incident T2DM. In addition, myomectomy seemed to attenuate the risk for incident T2DM in young women with UL.